2019
DOI: 10.1097/inf.0000000000002258
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Yersiniabactin-producing Klebsiella pneumoniae in a Neonatal Intensive Care Unit

Abstract: Background: The Gram-negative bacterium Klebsiella pneumoniae is a frequent pathogen causing outbreaks in neonatal intensive care units. Some Enterobacteriaceae can acquire the ability to sequester iron from infected tissue by secretion of iron-chelating compounds such as yersiniabactin. Here we describe an outbreak and clinical management of infections because of a highly virulent yersiniabactin-producing, nonmultiresistant K. pneumoniae strain in a neonatal intensive care unit. Outbreak investigation and eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
1
10
0
1
Order By: Relevance
“…BARNARDS isolates clustered with previously reported neonatal isolates, including ST45, ST48 and ST348 (refs. 15 , 22 , 23 ), but we also revealed distinct and new genetic lineages. The major AMR-related K. pneumoniae clades in Asia (ST11) and Europe (ST147 and ST307) 24 were also identified in this study.…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…BARNARDS isolates clustered with previously reported neonatal isolates, including ST45, ST48 and ST348 (refs. 15 , 22 , 23 ), but we also revealed distinct and new genetic lineages. The major AMR-related K. pneumoniae clades in Asia (ST11) and Europe (ST147 and ST307) 24 were also identified in this study.…”
Section: Resultsmentioning
confidence: 55%
“…K. pneumoniae is an important cause of neonatal sepsis in LMICs; however, there are few data analysing this species beyond antimicrobial susceptibility testing. Here, we have shown that K. pneumoniae was the most frequently identified GNB; therefore, the genomic diversity of this collection was scrutinized to contextualize these isolates, both within this study collection and within previously known collections 15 , 16 , 22 , 23 . K. pneumoniae ( n = 258) was found at all clinical sites (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a finding simplifies the diagnosis of pathogenic bacteria significantly. The role of yersiniabactin (Ybt) in mediating the virulence of human pathogenic bacteria is unquestionable: (i) invasive enteric bacteria from the genera Yersinia, Escherichia, and Klebsiella secrete Ybt during human infection to combat host-mediated metal deficiencies 13 ; (ii) comparative genomics revealed that the list of horizontally transferred gene sets in Salmonella enterica is dominated by virulence factors and the yersiniabactin gene cluster 14 , suggesting an important role of this siderophore in human pathogenicity; and (iii) in addition to uropathogenic enterobacteria expressing Ybt 13 , it was shown very recently that all isolates of Klebsiella pneumoniae from infant blood or stool samples taken during outbreaks in neonatal intensive care units produced Ybt 15 .…”
Section: Discussionmentioning
confidence: 99%